THE ROLE OF FUNCTIONAL FOODS FOR HEALTHY LIFE: CURRENT PERSPECTIVES - RAJESH KUMAR; SEEMA BHAYANA; SONIA KAPOOR (International Journal of Pharma and Bio Sciences, 2015)
Role of diet beyond basic nutrition in supporting health and prevention of diseases has been clearly established. This has led to the development of a different category of foods called functional foods. Secondary metabolites present in these foods have a role in preventing life threatening chronic diseases like cardiovascular diseases, diabetes, obesity, hypertension, arthritis, cancer as well as various health benefits such as performance enhancement, stress relief, anti-inflammatory, immunomodulation and increase of memory. Various classes of functional foods like cereals, legumes, fruits, vegetables, milk based foods, fortified foods, eggs, green tea, and cocoa are rich sources of antioxidants, fibers, acids of therapeutic and curative potential which keep away various malignancies and disorders in the body. This review aims to emphasize the therapeutic properties of all types of foods like cereals and pulses, fruits and vegetables, dairy products, tea etc. which form a part of routine diet.